4X4 MIMO slot antenna spanner shaped low mutual coupling for Wi-Fi 6 and 5G communications - Noora Salim; Mandeep S. J Singh; Amer T. Abed; Mohammad Tariqul Islam (Alexandria Engineering Journal, 2023)
Multiple-input multiple-output (MIMO) antennas are essential for modern wireless communication systems that require high data rates, reliability, and quality. However, designing MIMO antennas poses several challenges, such as achieving high isolation, low mutual coupling, low envelope correlation coefficient (ECC), high gain, and high efficiency in a compact size. In this paper, we propose a novel MIMO antenna design that can overcome these challenges and support various wireless applications, such as WiFi-6, 5G (n77/n78/n79), and satellite communications. The proposed design consists of four spanner-shaped radiating elements that are etched on an FR-4 substrate with a tapered feeding line. The spanner-shaped antenna is derived from an octagonal ellipse that is cut by another octagonal ellipse to form the shape of the antenna. The proposed design achieves dual operating bands of 3.3–3.8 GHz and 4.5–8.4 GHz with low mutual coupling (<−10 dB), low ECC (less than0.05), high gain (up to 4 dBi), and high efficiency (>80%). The proposed design is compared with other MIMO antenna designs in the literature and shows its advantages in terms of size, performance, and applicability.